Interfaces entre ciência e literatura em livros juvenis e suas contribuições ao ensino de ciências - ALVARENGA, Glaziane Soares (2022)
The use of literature in Science teaching has fundamental relevance to the educational process. In the development of teaching practices, it is necessary to offer materials that support teaching and learning, contributing to the systematization of contents and the teacher's work. Thus, this work focuses on the following research problem: How are the relations between science and literature processed in youth books that present scientist profiles and in what ways can they contribute to the Science teaching? In this perspective, has like general objective: to analyze the relations between science and literature, from juvenile books, in view of their contributions to the Science teaching. And, like specific objectives: to identify the textual genres present in the analyzed works; to check the approaches carried out on the history of science; to analyze the profiles of scientific presented by the works. This research has a qualitative approach, the investigation being conducted from the procedures of content analysis, based on Bardin (2016), using references present in the literature for the elaboration of the analysis categories, linked to textual genres, to the history of science, having as reference the work of Campos and Cachapuz (1997), and to the profiles of the portrayed scientists, categories proposed by Queiroz and Rocha (2021) were used. As for the books analyzed, it is clear that they portray historical elements of the periods presented, highlighting the social context in which each scientist developed their main scientific ideas and inventions. However, it is possible to verify both the presence of elements that demonstrate science as a historical product and carried out collectively, as well as the presence of reports that disagree with this aspect, not demonstrating the limitations and complexity of scientific work. Regarding the profiles of scientists, there is an alternation between the perspectives presented by the analyzed material, being concentrated mainly between the views of scientists as genius, idealist and/or adventurer. The materials are well illustrated and attractive, demonstrating possibilities for use in Science teaching practices. However, it is relevant to problematize some aspects present in these materials, demystifying views about scientists and about science, which needs to be seen as a social, collective and historical construction of humanity. Keywords: